Respuesta :

309445

Answer:

No real solutions.

Step-by-step explanation:

Let's solve your equation step-by-step.

11x2−5x+2=0

For this equation: a=11, b=-5, c=2

11x2+−5x+2=0

Step 1: Use quadratic formula with a=11, b=-5, c=2.

x=

−b±√b2−4ac

2a

x=

−(−5)±√(−5)2−4(11)(2)

2(11)

x=

5±√−63

22

Answer:

see explanation

Step-by-step explanation:

11x² - 5x + 2 = 0 ← in standard form with

a = 11, b = - 5 , c = 2

Solve using the quadratic formula

x = [tex]\frac{-b+/-\sqrt{b^2-4ac} }{2a}[/tex]

  = [tex]\frac{5+/-\sqrt{((-5)^2-(4(11)(2)} }{2(11)}[/tex]

 = [tex]\frac{5+/-\sqrt{25-88} }{22}[/tex]

 = [tex]\frac{5+/-\sqrt{-63} }{22}[/tex]

 = [tex]\frac{5+/-\sqrt{9(-1)(7)} }{22}[/tex]

 = [tex]\frac{5+/-3i\sqrt{7} }{22}[/tex]

Then

x = [tex]\frac{5}{22}[/tex] - [tex]\frac{3}{22}[/tex] i[tex]\sqrt{7}[/tex] , [tex]\frac{5}{22}[/tex] + [tex]\frac{3}{22}[/tex] i[tex]\sqrt{7}[/tex]

ACCESS MORE